COMPARISON OF FINANCIAL PERFORMANCE OF CONVENTIONAL BNI (BNIK) AND BNI SYARIAH (BNIS): REVIEW BEFORE AND DURING COVID-19 - Habibi, Ahmad; Normasyhuri, Khavid; Anggraeni, Erike (Jurnal Ekonomi Balance, 2021)
Covid-19 is a disease that spreads across continents across countries and even Indonesia. The Covid-19 pandemic has become a challenge for the business world, including banks such as Conventional BNI (BNIK) and Sharia BNI (BNIS). In its implementation, financial performance is an important measure of whether in the company there is an increase in the company's finances or vice versa. This study aims to compare the financial performance of profitability ratios, namely ROA, ROE, and BOPO Conventional BNI (BNIK) and Sharia BNI (BNIS) before and during covid-19. This research is included in quantitative research with comparative nature. The type of data used is secondary data obtained from the official website of the Financial Services Authority (OJK). The statistical tool used is SPSS Version 21 using the Mann-Whitney test. Research result Shows that before Covid-19 there were differences in the financial performance of the two banks, namely Conventional BNI (BNIK) and Sharia BNI (BNIS) and it appears that financial performance from the ROA, ROE, and BOPO aspects of Conventional BNI (BNIK) is still better than Sharia BNI (BNIS) before covid-19. Then during covid-19, there was no difference in the financial performance of the two banks, namely Conventional BNI (BNIK) and Sharia BNI (BNIS) and it was seen that the Covid-19 pandemic certainly had an impact on financial performance in terms of ROA, ROE, and BOPO aspects, both conventional and sharia bank.